2000
DOI: 10.1111/1467-9310.00190
|View full text |Cite
|
Sign up to set email alerts
|

R&D as a business – what are the implications for performance measurement?

Abstract: There have been considerable changes in the way that Research and Development (R&D) has been managed over recent years, many of which have been influenced by the external environment. These have been discussed in a number of publications with much of the debate centring around the movement from the so-called first generation to fifth generation models of R&D management.What has not been debated to the same extent are the implications of recent and likely future trends in R&D management for the way performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…In this context, PM on R&D helps to creates links between the organisation's strategy and R&D by translating the organisation's strategy into performance measures which could, in turn, be linked to R&D activities. A number of studies have revealed that PM of R&D plays a vital role by influencing and helping organisations to implement their strategies (Bremser and Barsky, 2004;Pearson et al, 2000;Kerssens-van Drongelen et al, 2000;Kerssens-van Drongelen and Bilderbeek, 1999;Werner and Souder, 1997;Brown and Svenson, 1988). Yawson et al (2006) argue that PM for R&D activities provide the basis to assess whether the organisation is progressing towards its goals, identifies the strengths and weaknesses, decides on the future actions needed for improvements and provides data to request additional resources hence facilitating the implementation strategies.…”
Section: Value Of Performance Measurement For Research and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, PM on R&D helps to creates links between the organisation's strategy and R&D by translating the organisation's strategy into performance measures which could, in turn, be linked to R&D activities. A number of studies have revealed that PM of R&D plays a vital role by influencing and helping organisations to implement their strategies (Bremser and Barsky, 2004;Pearson et al, 2000;Kerssens-van Drongelen et al, 2000;Kerssens-van Drongelen and Bilderbeek, 1999;Werner and Souder, 1997;Brown and Svenson, 1988). Yawson et al (2006) argue that PM for R&D activities provide the basis to assess whether the organisation is progressing towards its goals, identifies the strengths and weaknesses, decides on the future actions needed for improvements and provides data to request additional resources hence facilitating the implementation strategies.…”
Section: Value Of Performance Measurement For Research and Developmentmentioning
confidence: 99%
“…Concerns of investors and shareholders on R&D spending have demanded identification of the actual contribution from R&D investments towards the organisational goals, thus increasing the accountability of the proper usage of R&D investments (Osawa and Yamasaki, 2005).Therefore, Pearson et al (2000) and Nixon (1998) state that management has been forced to find ways to measure the return on R&D expenditure and to evaluate the performance of such activities. In addition to the identification of utilisation of resources, PM in R&D could identify the proper resource allocation within organisations (Bremser and Barsky, 2004;Pearson et al, 2000;Kerssen-van Drongelen and Bilderbeek, 1999). Furthermore, PM in R&D improves communication and coordination of the activities (Bremser and Barsky, 2004;Loch and Tapper, 2002).…”
Section: Value Of Performance Measurement For Research and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…That study has been of considerable assistance to us in the final choice of the indicators proposed for the BSC in the University, although we have modified the strategic perspective, drawing on the model used for the financing of the public universities of Andalusia. Perhaps one very important factor in explaining the proliferation of different performance measurements in the University, and the lack of consensus on these, is that, while it is recognized that the two main areas of activity, teaching and research, should be aligned with the strategy of the Institution [2][3][4][5], in practice, few contributions have been published in respect of the measurement of academic research output that display its full complexity and show how it can, in fact, be aligned with the strategy of the organisation.…”
Section: The Balanced Scorecard As An Instrument Of Measurement Of Pementioning
confidence: 99%
“…[5] reviewed the literature and reports on measurements of R & D performance; they advised the joint use of traditional techniques of measurement of returns focussed on controlling the costs of this type of activity, with strategic measurements in the longer term. For this process of integration, the application of a BSC is suggested.…”
Section: The Balanced Scorecard As An Instrument Of Measurement Of Pementioning
confidence: 99%